RISK AND THE MANAGEMENT OF A HEALTHCARE UNIT – A LITERATURE REVIEW - SZEWCZUK, ANDRZEJ; ŁUGOWSKA, EMILIA MAGDALENA; KRUTH, JARI (Management and Administration Journal, 2021)
Due to its specific nature, the provision of medical services is associated with considerable risk; and it is extremely important to diagnose and manage this same risk. Healthcare entities should be covered by appropriate instruments that reduce risk and support quality. In addition to legal regulations that must be met by entities providing such services, there are systemic solutions that are being implemented by more and more healthcare entities. The article analyses the risk that occurs in the management of a health care unit. In the first part of the article, the literature on the topic is reviewed, whereas what follows thereafter analyses risks in the management of a healthcare unit, including risk factors and risk allocation. The conclusion points to the risks which play the greatest role in the management of medical service providers; and enumerates some of the most important issues of risk management in medical entities.